Correlating Communication and Time Management: Keys to Counselor Effectiveness - Abubakar, Abdulkareem Olalekan; Tiamiyu, Kamoru Abidoye; Abdulkareem, Habibat Bolanle (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2025)
The study utilized a correlation research design and employed the Simple Random Sampling Technique to select 100 counselors. Data were gathered using scales developed by Cameron, Berling, and Kataria, which respectively measured Communication Skills (CSS), Time Management Skills (TMS), and Effective Service Delivery Skills (ESDS). Statistical analyses included Pearson Product-Moment Correlation (PPMC) and Multiple Regression, with a significance level set at 0.05. Results indicated a significant positive correlation between communication skills and effective service delivery (r = 0.64, df = 198, p 0.05), as well as between time management and effective service delivery (r = 0.64, df = 198, p 0.05). Furthermore, there was a significant combined contribution of communication skills and time management to effective service delivery (Adjusted R^2 = 0.59, df = 2/97, F = 71.13, p 0.05). Communication skills (β = 0.47) and time management (β = 0.46) both made significant relative contributions to effective service delivery among counselors.